Mind: the gap – to advance CSR research, think about stakeholder cognition. Issue 1 (3rd May 2016) - L. Barnett, Michael
Abstract : Purpose: The purpose of this paper is to develop a better understanding of how, and how well, stakeholders make decisions about rewarding firms for acts of social responsibility and punish firms for their lack thereof. Design/methodology/approach: The author integrates factors at the individual, firm, and industry levels that cause variation in how stakeholders attend to corporate social (ir)responsibility. Findings: The author explicates the multi-level cognitive process stakeholders undertake in attending to firm's actions and identifies limits on their ability to fulfill their central role in conditioning firms to be more socially responsible. Research limitations/implications: The author outlines areas for future research that can fill gaps in the understanding of how stakeholders notice, make sense of, and respond to corporate social practices. Social implications: The author argues that, under many conditions, business case or self-regulatory solutions may be inadequate to increase corporate social responsibility (CSR), and instead, formal regulatory solutions may prove necessary. Originality/value: This paper brings needed structure to the literature on CSR. By delving deeper into the minds of stakeholders and outlining a multi-level cognitive process, it enables scholars to better address the key managerial issue of when, not simply whether, it pays to be good.